Draftbility of Power Tiller with Different Lug Angle of Cage Wheels in Puddle Soils for Paddy - Pradhan, Piyush; Verma, A. K.; Naik, R. K.; Guru, P. K. (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted on IGKV research farm in wet puddle condition in April month of 2015. The wet tillage practice was carried out by power tiller cage wheel attached with five tines cultivator. Paddy production increases by puddling of soil before transplanting. Cage wheel is an important traction device for any prime mower. The lug is wing provided in cage wheels which interact with the wet soil to churn the soil .The cage wheel 730 mm diameter with 30⁰, 45⁰, and 60⁰ lug angle and three different diameter of 73 mm, 680 mm and 780 mm of 30⁰ was tested at 0 to 50 mm, 50 to 100 mm, 100 to 150 mm and 150 to 200 mm, depth of water level in wet land field. The result was found that cage wheel C1 of 30⁰ lug angle with 730 mm diameter give better performance than other cage wheel. The cage wheel showed the best result in 50–100 mm water level in respect to maximum tractive efficiency was found in the range of 73−78% at 996 N to 1009 N draft and drawbar power was in the range of 478.08 W to 484.32 W. While maximum drawbar power was (523.16 to 555.28 W) was observed at 0 to 50 mm water level. Therefore cage wheel of 30⁰ lug angle with 730 mm diameter was found suitable for wet land paddy field condition.